2023
DOI: 10.1007/s12686-023-01303-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased sample size provides novel insights into population structure of Mediterranean loggerhead sea turtles

Abstract: The loggerhead sea turtle (Caretta caretta), has the broadest distribution among sea turtle species in the Mediterranean and requires regional and international collaborations in addition to local efforts to better inform conservation actions. Molecular techniques are powerful tools to assess population dynamics at large scales, especially by determining the connectivity among different nesting and foraging sites, and genetic diversity. In this study, a large sample was collected synchronously in the nesting a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The total numbers of individuals (alive and stranded) were taken into consideration for the identification of populations' distribution to determine the significance of each selected study area for nesting foraging or both. As per Kaska et al, 4 Casale et al, 5 and Hochscheid et al, 6 the Egyptian Mediterranean coast might not be one of the important nesting areas in the Mediterranean, but it is known to be one of the most important areas as feeding ground and migratory corridors 7 in the Mediterranean basin. The studied areas of the Egyptian Mediterranean coast showed habitat fragmentation in the most of north coast areas due to massive touristic development and unplanned urbanization over the past 40 years.…”
Section: B Identification Of Regular Nesting Sites and Population Dis...mentioning
confidence: 79%
“…The total numbers of individuals (alive and stranded) were taken into consideration for the identification of populations' distribution to determine the significance of each selected study area for nesting foraging or both. As per Kaska et al, 4 Casale et al, 5 and Hochscheid et al, 6 the Egyptian Mediterranean coast might not be one of the important nesting areas in the Mediterranean, but it is known to be one of the most important areas as feeding ground and migratory corridors 7 in the Mediterranean basin. The studied areas of the Egyptian Mediterranean coast showed habitat fragmentation in the most of north coast areas due to massive touristic development and unplanned urbanization over the past 40 years.…”
Section: B Identification Of Regular Nesting Sites and Population Dis...mentioning
confidence: 79%
“…Genetic data from the eight analysed nests indicated that the most common mtDNA CR haplotype is CC-A2.1, which is commonly proposed as the ancestral lineage for the Mediterranean Sea and was possibly introduced from the Atlantic Ocean by colonizing females in the last post-glacial period [ 20 , 21 , 41 , 55 ]. Currently, CC-A2.1 is the most commonly encountered haplotype, present in more than 60% of the free-living Mediterranean loggerhead sea turtles [ 21 , 56 , 57 , 58 , 59 , 60 ]. This haplotype dominates most Mediterranean nests and has been detected in all nesting areas studied [ 22 , 41 , 59 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, CC-A2.1 is the most commonly encountered haplotype, present in more than 60% of the free-living Mediterranean loggerhead sea turtles [ 21 , 56 , 57 , 58 , 59 , 60 ]. This haplotype dominates most Mediterranean nests and has been detected in all nesting areas studied [ 22 , 41 , 59 , 61 , 62 ]. Haplotype CC-A3.1 is the second most commonly encountered haplotype in the Mediterranean Sea and accounts for around 20% of the free-living individuals studied [ 21 , 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The D-Loop sequences were aligned, cut and blasted with published haplotype sequences found in the database maintained by the Archie Carr Center for Sea Turtle Research ( https://accstr.ufl.edu/ ) using BIOEDIT 89 . We identified the regular nesting region in which each haplotype was found following the haplotype frequencies found in previous studies 43 , 90 to determine the potential origin of the nesting females that laid each nest.…”
Section: Methodsmentioning
confidence: 99%